Design of LED constant current controller using multi-channel current-sharing topology. (November 2016) - Chen, Keng; Li, Ming; Xiao, Peng; Johnsen, Andrew
Abstract: In this study, a multi-channel current sharing topology controller is designed for LED lighting application. This controller can regulate three channels of LEDs. Each LED string may have a different forward voltage and current setting. A constant buck regulator is also integrated inside this controller to regulate the total current, which is fed into three LED output channels. The circuit also contains a feedback loop in order to precisely control the current passing through each LED string and is immune to transient conditions. The start-up procedure is designed to ensure both acceptable overshooting of output current and that the turn on time is as short as possible. In the final simulation, the maximum output current overshooting and ripple under transient condition do not exceed 20% of the nominal value. The output current buildup time is less than 25 ms for all three channels. The design is laid out using 350 nm technology in a 1.5 mm×1.5 mm area. The chip does not contain a driver for power MOSFET.